MOTIVASI DALAM PERSPEKTIF PENDIDIKAN ISLAM - Rahmat Sholihin (CV. ADIBA AISHA AMIRA, 2022)
The ideal teacher (educator) is someone who succeeds in bringing students (students) to achieve goals and maximum results. To achieve the effectiveness of a lesson, a professional, competent and expert teacher is needed and has good teaching skills.